KARAKTERISASI SIFAT FISIKO - KIMIA PATI TALAS KIMPUL (Xanthosoma sagittifolium) TERMODIFIKASI DENGAN METODE ASETILASI - Widiawan, I Made Edi; Nocianitri, K.A; Putra, Nengah Kencana (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2013)
Research aims to find the effects of acetic anhydride concentration and soaking time on the physico-chemical properties of modified cocoyam starch and to determine the optimal concentration of acetic anhydride and a soaking time that can produced the best physico – chemical properties of modified cocoyam starch. This study was an experimental study designed by Randomized Block Design (RBD), with a factorial experiment, comprised of two factors there was acetic anhydride concentration (factor I) consisting three levels (1%, 2% and 3%), and soaking time (factor II) consisting three levels (95, 105, and 115 minutes. Parameters observed were substitution degree, starch content, amylose content, swelling power, solubility and clarity of pasta. The results showed that concentration of acetic anhydride and a soaking time highly significant effeted the physico-chemical properties of modified cocoyam starch. Acetylation modifications improved the characteristics of modified cocoyam starches such as degree of substitution, starch content, amylose content, solubility, and swelling power. The best physico chemical properties of modified cocoyam starch was produced by 3% of acetic anhydride concentration, and soaking time for 115 minutes with a degree of substitution of 1.0585, starch content of 91.82%, amylose content of 34.82%, solubility of 29.80%, swelling power of 21.57 %, clarity of pasta on the first day was 0.66, and clarity of pasta on eighth day was 0.23.
Keywords: physico-chemical properties, starch, cocoyam, acetylating, acetic anhydride